2020
DOI: 10.1111/jnu.12607
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Capital and the Occupational Psychologic Risks of Nurses: The Mediation Role of Compassion Satisfaction

Abstract: PurposeThe aim of the study was to explore the relationship between psychological capital (hope, self‐efficacy, resilience, and optimism) and burnout and compassion fatigue or secondary traumatic stress among general hospital nurses, and the mediating role of compassion satisfaction in this relationship.DesignCross‐sectional survey study. Participants were 697 nurses working in different nursing departments in tertiary university hospitals in a metropolitan city in Turkey.MethodsThe semistructured interview fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
5
28
0
1
Order By: Relevance
“…It was determined that the nurses had low-level burnout, moderate-high compassion satisfaction, and low-moderate compassion fatigue symptoms. This result was also similar to previous studies [ 20 , 21 , 23 , 32 , 33 ]. Low-level anxiety, depression, somatization, hostility, and negative self-concept were detected.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was determined that the nurses had low-level burnout, moderate-high compassion satisfaction, and low-moderate compassion fatigue symptoms. This result was also similar to previous studies [ 20 , 21 , 23 , 32 , 33 ]. Low-level anxiety, depression, somatization, hostility, and negative self-concept were detected.…”
Section: Discussionsupporting
confidence: 93%
“…ProQoL is the kind of positive (compassion satisfaction) and negative (compassion fatigue and burnout) feeling that professionals feel as a result of having done their job well [ 12 ]. In our study, a positive correlation was found between compassion fatigue and burnout [ 4 , 18 , 20 , 21 , 41 44 ], and a negative correlation was found between compassion fatigue and compassion satisfaction [ 20 , 41 , 42 ], similar to other studies in the literature. In addition, it was found that there was a negative correlation between compassion satisfaction and burnout [ 18 , 20 22 , 41 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Numerous studies have confirmed that psychological capital and its interventions are related to reduced work-related problems, not to mention positive wellbeing and workrelated outcomes [96][97][98][99][100][101][102][103][104][105]. Research of the psychological capital in the public sector has evidenced its' numerous benefits [57,[106][107][108][109].…”
Section: Psychological Capitalmentioning
confidence: 99%
“…[4,12,13] Studies to date have shown that the COR theory is an explanatory model for understanding the stress process and burnout at work and limiting the resource loss is key to interventions to prevent or reduce stress. [14,15] The resource investment principle of the COR theory also highlights the importance of proactive coping. According to this theory, individuals or groups cope proactively by striving to acquire and maintain resource reservoirs, taking action early when the first warning signs of an impending problem are proven, and choosing to position themselves in conditions appropriate to their resource [13,16] reported that proactive coping directly reduces job stress, burnout, anger, and depression, and increases professional competence, work efficiency and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%